THE EFFECTS OF FOLIAR APPLICATION OF SOME SELECTED PHYTOHORMONES ON THE PROXIMATE, PHYTOCHEMICAL, AND MINERAL COMPOSITIONS OF ROSELLE (HIBISCUS SABDARIFFA L.) LEAVES - Keshinro, Olajide M.; Ogbe, Abdulazeez A.; Oreshile, Khadijat Y.; Omolokun, Kehinde T. (FUDMA JOURNAL OF SCIENCES, 2023)
Recent research has shown that agricultural crops can be improved through the use of phytohormones. In this study, we tested the effects of coconut water (CW), Gibberellic Acid (GA3), Indole Acetic Acid (IAA), 6-Benzylaminopurine (BAP), and Naphthalene Acetic Acid (NAA) through foliar spray, on the seedlings of Hibiscus sabdariffa L. (Roselle) to understand the best treatment to improve nutritional quality. Roselle seedlings were raised in 30cm × 19cm polythene bags and arranged using a completely randomized design in a screened house for 4 months. The phytohormones were applied as treatments on seedlings both singly and combined in the range of 10-20 (%) for CW and 50-200 (mg/L) for the other treatments. Proximate, vitamin C and mineral elements were determined using standard analytical procedures, while phytochemical screening was carried out on plant extracts. The best nutritional composition was achieved using 200mg/L GA3 and 20% CW with crude protein, fibre, vitamin C, and flavonoid contents of 4.17, 1.36, 46.7, and 3.72 mg/100g respectively. Treatments with 20% CW also recorded the highest calcium and magnesium contents of 193.20 and 89.20 mg/100 g respectively. Generally, the single hormone treatments outperformed the combined hormone treatments. The exceptional performance of CW proved that CW has the potential to improve the nutritional content of agricultural crops and can also serve as a cheap and accessible bio-stimulant for agricultural crops such as H. sabdariffa.
Keywords: foliar spray; phytohormones; phytochemical; roselle; proximate